Tinjauan Hukum Ekonomi Syari’ah terhadap Praktik E-Commerce dengan Sistem Pembayaran Kredit Shopee PayLater - Suwarno (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
The practice of payment through the credit system in the e-commerce industry, especially through platforms like Shopee PayLater, has become a phenomenon increasingly dominating modern business transactions. This article aims to provide an in-depth review regarding the